Evaluation of neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) in critical care patients with synthetic cannabinoid (bonzai) intoxication - Mustafa Kaplan; Alpaslan Tanoglu; Tolga Duzenli; Muhammet Yildirim; Yusuf Serdar Sakin; Musa Salmanoglu; Yalçin Önem (Egyptian Journal of Critical Care Medicine)
Abstract Objective Synthetic cannabinoid drug abuse has been dramatically increasing among young individuals in many countries. There have been reports of serious side effects with SC abuse in these patients. Previous researches have exhibited that neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) are associated with mortality and morbidity in many chronic diseases. The aim of this study was to evaluate PLR and NLR in critical care patients with synthetic cannabinoid (bonzai) intoxication. Materials and methods One hundred and seven synthetic cannabinoid intoxication patients requiring intensive care and 40 healthy controls were included in the study. Patients characteristics and the complete blood count (CBC) variables, including white blood cell (WBC), hemoglobin (Hb), platelet count, NLR, PLR as well as AST, ALT, albumin total bilirubin, and other routine biochemical parameters were tested. Data analyses were conducted with SPSS-15 software (SPSS Inc., Chicago, Illinois, USA). Statistical significance was set at a p-value of <0.05. Results All participants were male, and the mean age of the patients was 21.74 ± 1.57 and healthy controls was 22.62 ± 2.9 years (p > 0.05). All the routine laboratory tests and inflammatory markers (Erythrocyte sedimentation rate and C-reactive protein) were similar between groups. As complete blood cell count; mean WBC values were 9.43 ±3.27 × 103/mm3 vs 7.05 ±2.12 × 103/mm3 (p < 0.001), mean platelet counts were 237.33 ± 60 × 103/mm3 vs 263.90 ± 65.98 × 103/mm3 (p = 0.022), NLR counts were 3.17 ± 1.95 vs 2.32 ± 1.27 (p = 0.003) and PLR values were 114.43 ±36.39 vs 133.94 ±45.27 (p = 0.008), in patients and controls, respectively. Cardiac side effects were observed among 36 patients but nobody was died. Conclusion Our results exhibited a significant increase of NLR values and decrease of PLR counts among critical care patients with synthetic cannabinoid (bonzai) intoxication. After at least 24 h of intensive care stay without side effects, the patients might transfer out to inpatient clinic for ongoing follow up period and psychiatric consultation.